Sharing the burden: Empirical evidence on corporate tax incidence - Nadja Dwenger; Pia Rattenhuber; Viktor Steiner (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
This study assesses the burden of capital income tax passed onto labor through wage bargaining over economic rents, using estimations based on a unique pseudo-panel data set from Germany for the period 1998 to 2006. Tax return data cover the universe of corporations subject to corporate income tax, and labor market variables reflect the full record of employees covered by Social Security. We find that wage bargaining after a reduction in tax rates does not increase the wage bill if employment effects neglected by previous empirical studies are taken into account. Any increase in the total wage bill by higher wage rates set is equally compensated for by lower levels of employment. If adjustments in employment due to the increased user cost of capital are taken into account, a cut in corporate income taxes by 1 euro increases the wage bill by 0.47 euro. The identification of these effects comes from variation in the firm-specific average corporate tax rate across firms and over time resulting from two substantial tax reforms. The endogeneity of the firmspecific tax rate is controlled for by an instrumental variable approach. The instrument for the observed average tax rate is the counterfactual tax rate that a corporation would have faced in a particular period, had there been no endogenous change of its tax base, constructed using a detailed microsimulation model.
Keywords: H22; H25; J21; J31; H32; 330; tax incidence; wage determination; corporate income taxation; corporate tax return data